Perencanaan Fasilitas Tempat Wudhu Pria di Masjid Baitul Musyahadah Kota Banda Aceh - Fuady, Mirza; Buraida, Buraida; Munadi, Rizal; Triaputri, Allya; Kevin, M Andrian; Farrel, M Rafi (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
This community service activity aims to plan the construction of a men's ablution place at the Baitul Musyahadah Mosque. The main focus of the activity is to create ablution facilities that are ergonomic, hygienic, and in accordance with the increasing needs of worshippers. The methods used include interviews with mosque managers to explore information about the needs and constraints of facilities, field observations to analyze existing conditions, and the preparation of planning concepts based on local needs. The data obtained was processed to produce images of technical plans in the form of plans, appearances, and pieces of the men's ablution place. This planning pays attention to aspects of space efficiency, water flow, accessibility, and the selection of materials that are durable and easy to maintain. The results of this activity are expected to increase the comfort of worshippers in worship and become a reference for planning ablution facilities in other mosques that have similar needs.